TI_GERICHTE 12.2009.32 vom 22. Februar 2011 , Compravendita internazionale di merci - entità del prezzo - valuta del contratto - TI Tribunale d'appello (2011)
Compravendita internazionale di merci - entità del prezzo - valuta del contratto